The evolutionarily conserved BMP-binding protein Twisted gastrulation promotes BMP signalling - Oelgeschläger, Michael (2000)
Dorsal-ventral patterning in vertebrate and Drosophila embryos requires a conserved system of extracellular proteins to generate a positional information gradient. The components involved include bone morphogenetic proteins (BMP/Dpp), a BMP antagonist (Chordin/Short gastrulation; Chd/Sog) and a secreted metalloproteinase (Xolloid/Tolloid) that cleaves Chd/Sog. Here we describe Xenopus Twisted gastrulation (xTsg), another member of this signalling pathway. xTsg is expressed ventrally as part of the BMP-4 synexpression group and encodes a secreted BMP-binding protein that is a BMP signalling agonist. The data suggest a molecular mechanism by which xTsg dislodges latent BMPs bound to Chordin BMP-binding fragments generated by Xolloid cleavage, providing a permissive signal that allows high BMP signalling in the embryo. Drosophila Tsg also binds BMPs and is expressed dorsally, supporting the proposal that the dorsal-ventral axis was inverted in the course of animal evolution.